The impacts of participatory guarantee systems on farmers who produce local specialties : evidence from the North of Vietnam - Vo Doan Anh Thu; Zulfiqar, Farhad; Himanshu, Sushil Kumar; Yaseen, Muhammad; Junaid, Muhammad; Asian Development Bank{u2013}Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
Small-scale farmers who try to take advantage of organic production and local food trends find it challenging to acquire organic certifications from third parties due to their lack of finance and management capacity. The Participatory Guarantee System (PGS) which focuses more on different stakeholders{u2019} participation and farmers{u2019} capacity building is considered an alternative solution for smallholders. After 15 years of being applied in Vietnam, PGS has been increasingly developed in more than 10 provinces and is reported to bring plenty of benefits to smallholders. To have a holistic evaluation of the adoption of this model in Vietnam, this thesis employed surveys with 128 farmers (64 adopters and 64 non-adopters) and 5 in-depth interviews to assess the economic and social sustainability of PGS as well as its impacts on market access and income of producers of local specialties. The results show that PGS adoption created positive differences in the farmers{u2019} Economic Resilience, Social Well-being, and Market Access. As regards economic resilience, PGS farmers scored better in Community investment, Profitability, Product diversification, Stability of the market, Product quality, and information. PGS farmers had higher scores in Social Well-being in terms of Quality of life, Capacity development, Fair trading practices, Human health, and safety. In addition, PGS adopters witnessed improvements in half of the market access indicators, especially in Input support, Access to guaranteed output market, Value addition {u2013} Certification, Price premium, Access to the packaging facility, and Training. Besides, the data analysis proved a correlation between net income and PGS training. In terms of income, while there was almost no gap between the income of PGS and non-PGS producers of citrus fruit in Tuyen Quang and Hoa Binh province, the PGS rice producers in Bac Kan province could have a much higher benefit-cost ratio (or BCR) than their non-PGS counterparts. The results imply that PGS, or the Participatory Guarantee System is an advantageous model for smallholders to enhance their market access and earnings. However, to guarantee this income improvement, it is vital that PGS promote producers' autonomy in input supply and minimize marketing costs, especially the operation costs within the system.
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Agribusiness Management in Agribusiness Management
Thesis (M. Am.) - Asian Institute of Technology, 2024
Keywords: Quality assurance -- Vietnam; Agriculture -- Economic aspects -- Vietnam